The effects of application of iontophoresis and phonophoresis in patients with subacromial impingement syndrome - Yıldız, Ayfer; Kuşan, Elif (BMJ Publishing Group, 2017)
Background: Subacromial impingement syndrome (SIS) is defined as themechanical compression of subacromial structures between the coraco-acromialarch and the humerus during active elevation of the arm above shoulder height.Objectives: The aim of the study was to investigate the effects of applicationsof iontophoresis and phonophoresis, which has been used in addition tophysiotherapy program on pain and disability level in patients with SIS.
Keywords: Subacromial Impingement Syndrome; Iontophoresis; Phonophoresis